Tangled Mobilities Places, Affects, and Personhood across Social Spheres in Asian Migration (Volume 12) - Fresnoza-Flot, Asuncion; Liu-Farrer, Gracia (Berghahn Books, 2022)
The emotional, social, and economic challenges faced by migrants and their families are interconnected through complex decisions related to mobility. Tangled Mobilities examines the different crisscrossing and intersecting mobilities in the lives of Asian migrants, their family members across Asia and Europe, and the social spaces connecting these regions. In exploring how the migratory process unfolds in different stages of migrants' lives, the chapters in this collected volume broaden perspectives on mobility, offering insight into the way places, affects, and personhood are shaped by and connected to it.